The scientific journal as a social network and as a network of collaborators (Ágora de Heterodoxias, 2023)
The idea of a scientific journal as a social network for academic researchers is interesting and increasingly feasible thanks to digital communication tools and online collaboration. Although scientific journals have traditionally been used for research publication, they also have the ability to facilitate collaboration and a community among researchers. In a "social" scientific journal, researchers would be able to interact with their co-authors, colleagues, and other researchers through online comments, discussions, and comparison of notes.
Keywords: The scientific journal; Social network; Network of collaborators